PATHOLOGY OF THE HEMOSTATIC SYSTEM - P. F. Litvitskii ("Paediatrician" Publishers LLC, 2014)
In the lecture the most clinically significant forms of pathology of the hemostatic system, their reasons and key features for their development, symptoms and principles of treatment are discussed. Tests and special cases are attached to the lecture for assessment the learning level of the given material, and also reasoned variants of replies.